Insurrectionist wisdoms: toward a North American indigenized pastoral theology - Ferreras, Marlene M. (Environment and religion in feminist-womanist, queer, and indigenous perspectives, 2023)
"Through practical theological and anthro/gynopological methods, Insurrectionist Wisdoms offers an analysis of the situation of working-class Maya mexicanas living in Yucatán, México, working on the assembly line of a multinational corporation"--